2017
DOI: 10.15291/geoadria.115
|View full text |Cite
|
Sign up to set email alerts
|

Suvremene promjene klime i smanjenje protoka Save u Zagrebu

Abstract: Correlation coefficient of 0.81 between Sava River flow through Zagreb and precipitation in Ljubljana points at dominant significance of precipitation. In the warmest months Sava flow is very much dependent on evapotranspiration. Sava River flow has downward trend, and two intervals can be sharply distinguished: 1926-1959 and 1960-1995. That is the result of the identical precipitation trend at the Upper Sava. There is the trend of atmospheric pressure rise in the entire observed period. "Precipitation contine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Hydrological research on the part of the Sava River that flows through Croatia mainly focused on the changes in floods at the Zagreb gauging station, where it was concluded that the discharge regime is under the influence of engineering works carried out as part of the flood protection system of the Zagreb city area [48][49][50][51][52]. Moreover, Segota and Filpcic [53] reported that the discharge regime at the Zagreb gauging station is linked to scientifically observed climate changes, while Oresic et al [54] extended that conclusion to the middle section of the Sava River in the 1931-2010 period. Additionally, the analysis of flood waves along the middle course showed strong variability on multiple scales [55,56] and a preliminary approach to clustering of flood hydrograph shapes was conducted at gauging station Zagreb [57].…”
Section: Study Area and Datamentioning
confidence: 99%
“…Hydrological research on the part of the Sava River that flows through Croatia mainly focused on the changes in floods at the Zagreb gauging station, where it was concluded that the discharge regime is under the influence of engineering works carried out as part of the flood protection system of the Zagreb city area [48][49][50][51][52]. Moreover, Segota and Filpcic [53] reported that the discharge regime at the Zagreb gauging station is linked to scientifically observed climate changes, while Oresic et al [54] extended that conclusion to the middle section of the Sava River in the 1931-2010 period. Additionally, the analysis of flood waves along the middle course showed strong variability on multiple scales [55,56] and a preliminary approach to clustering of flood hydrograph shapes was conducted at gauging station Zagreb [57].…”
Section: Study Area and Datamentioning
confidence: 99%
“…(Čanjevac, 2012) At the national level (and level of large regions of Croatia), certain climatic changes have already been recorded, and their influence on changes in the water balance observed (Bonacci and Gereš, 2001;Pandžić et al, 2009) or their influence on changes of the discharge regime (Gajić-Čapka and Cesarec, 2010;Čanjevac, 2012;Barbalić and Kuspilić, 2014;Čanjevac and Orešić, 2015;2018). Changes to discharge on the Sava River were examined by Bonacci and Ljubenkov (2004), Šegota and Filipčić (2007), Trninić and Bošnjak (2009), Bonacci and Oskoruš (2011) and Orešić et al (2017), while changes on the Drava River by Bonacci and Oskoruš (2010) and Gajić-Čapka and Cesarec (2010). This paper contains a hydrological analysis of the Danube regime using measured flow data at four regression stations; regression station Batina in the Republic of Croatia, and the regression stations Bezdan, Bogojevo and Smederevo in the Republic of Serbia for the period 1992-2018.…”
Section: Introductionmentioning
confidence: 99%